Phytoplankton Community in The Lembeh Strait, Bitung and Wori Beach, Manado, North of Sulawesi, Indonesia - Hikmah Thoha; Mariana D Bayu; Arief Rachman; Tan Senming (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2019)
This study was conducted to understand phytoplankton community in the Lembeh Strait at Bitung and Wori Beach at Manado in October 2015. The phytoplankton samples were collected with vertical towing using Kitahara plankton net (mesh size 80 µm). Identification and enumeration were done using Sedgwick Rafter Counting Chamber (SRCC) under 100-400X magnification. Phytoplankton abundance in Wori, Manado were lower than Lembeh Strait. There were 24 genera of diatom group and nine genera of dinoflagellate group found in Wori and Lembeh Island waters. Total phytoplankton abundance in Wori ranged from 16,293.28 – 464,358.45 cells m-3 (station 6 and station 5, respectively). Whilst, In Lembeh Strait, Bitung, the highest abundance of phytoplankton was 2,300,407.33 cells m-3 and the lowest was 16,089.61 cells m-3. The composition of diatoms and dinoflagellates in Wori and Lembeh Strait was dominated by diatom which ranged from 80.70 % to 100.0%. Based on the mean contribution at each station among the two locations, there were 11 dominance genera of diatom and dinoflagellate groups which the mean contribution value above five percent. Those were including six genera of diatom group (Chaetoceros, Bacteriastrum, Nitzchia, Rhizosoleria, Thalassiothrix, and Thalassiosira) and five genera of dinoflagellate group (Ceratium, Prorocentrum, Protoperidinium, Pyrodinium, and Scriepsiella, Chaetoceros (diatom) and Protoperidinium (dinoflagellate) exhibit the highest genera representation in all diatom and dinoflagellate group among the two locations, with a 38 % and 36 % (respectively) mean contribution. Three genera which commonly known to cause harmful algal blooms (HABs) were observed in those two locations. Nitzschia from diatom group, Prorocentrum, and Pyrodinium from dinoflagellate group. Nitzschia was the most frequently found, almost recorded at all station in Wori, Manado and Lembeh strait, Bitung. The less frequent found of HABs causative organisms in those two locations was Pyrodinium.